PENGARUH KOMPETENSI DAN PELATIHAN TERHADAP PRESTASI KERJA PEGAWAI PT. SINAR MENARA DELI MEDAN - HAPOSAN HUTAHAEAN (LP2MTBM MAKARIOZ, 2020)
This research aims to test the influence of competence and training on the work achievement of employees of PT. SinarMenara Deli Medan. The type of research used is quantitative research. The study used the census method with thequestionnaire instrument, the sampling technique in the study using probability sampling technique using total sampling, sothat the sample was 85 people. Processing techniques and data analysis using validity tests, reliability tests, classicalassumption tests, descriptive analysis, cross tabulation, multiple linear regression analyses, and coefficient of determinationanalysis. The results showed that individually competence employees have significant effect on the work achievement ofemployees of PT. Sinar Menara Deli Medan and significant impact training and is the dominant variable to the workachievement of employees of PT. Sinar Menara Deli Medan. Competency and training results jointly significant impact on thework achievement of employees of PT. Sinar Menara Deli Medan. The value of RSquare is 0.751 or 75.10%, which meansthat the research variable contributes greatly to the contribution of the employee achievement of PT. Sinar Menara DeliMedan as big as 75.10% while the remaining 24.90% is influenced by other factors outside this research.